2023
DOI: 10.1021/acsami.2c22694
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-Based Solid-State Gel Polymer Electrolyte for Lithium–Oxygen Batteries with a Long-Cycling Life

Abstract: Metal–air batteries have attracted wide interest owing to their ultrahigh theoretical energy densities, particularly for lithium–oxygen batteries. One of the challenges inhibiting the practical application of lithium–oxygen batteries is the unavoidable liquid electrolyte evaporation accompanying oxygen fluxion in the semi-open system, which leads to safety issues and poor cyclic performance. To address these issues, we propose a solid-state polyimide based gel polymer electrolyte (PI@GPE), immobilizing and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Lithium-oxygen batteries (LOBs) have received increasing attention due to their representative high specific capacity and energy density, which far exceed other available battery systems. With the advantages of simple composition, high dissolved oxygen content, and good wettability, organic liquid electrolytes (LEs) are often the first choice. However, due to the open working environment of LOBs, LEs have hidden dangers of leakage and volatilization. Moreover, LEs may decompose in the presence of intermediate products. Although solid-state electrolytes (SSEs) can avoid well the risks of LEs and improve the safety of the cells, the low ionic conductivity of polymer solid electrolytes and the high interfacial resistance of inorganic solid electrolytes greatly hinder the practical applications. , Gel polymer electrolytes (GPEs), which immobilize and preserve the LEs in the gelled polymer substrate, combine the good mechanical properties of polymer frameworks with the high ionic conductivity and good interfacial properties of organic LEs, which are considered as promising candidates for high-performance LOBs. …”
Section: Introductionmentioning
confidence: 99%
“…Lithium-oxygen batteries (LOBs) have received increasing attention due to their representative high specific capacity and energy density, which far exceed other available battery systems. With the advantages of simple composition, high dissolved oxygen content, and good wettability, organic liquid electrolytes (LEs) are often the first choice. However, due to the open working environment of LOBs, LEs have hidden dangers of leakage and volatilization. Moreover, LEs may decompose in the presence of intermediate products. Although solid-state electrolytes (SSEs) can avoid well the risks of LEs and improve the safety of the cells, the low ionic conductivity of polymer solid electrolytes and the high interfacial resistance of inorganic solid electrolytes greatly hinder the practical applications. , Gel polymer electrolytes (GPEs), which immobilize and preserve the LEs in the gelled polymer substrate, combine the good mechanical properties of polymer frameworks with the high ionic conductivity and good interfacial properties of organic LEs, which are considered as promising candidates for high-performance LOBs. …”
Section: Introductionmentioning
confidence: 99%
“…However, compared with LEs, there was still a certain gap in the discharge performance and galvanostatic cycling stability. Therefore, inorganic fillers are introduced to construct hybrid gel polymer electrolytes (HGPEs), which provide multiple paths for ion transport, thereby improving the electrochemical performance. Relatively, among a series of inorganic fillers, Li 1+ x Al x Ge 2– x (PO 4 ) 3 (LAGP), a typical NASICON-type solid electrolyte, exhibits high ionic conductivity comparable to that of LEs at room temperature and excellent stability toward water and air. , Croce and Maier et al confirmed the Lewis acid–base interaction between LAGP and anions gained from lithium salts in the composite polymer electrolytes and nonaqueous liquid electrolytes, respectively. The above interactions increase the proportion of “free” Li + , which can move rapidly throughout the conducting pathways, making the electrolytes exhibit high ionic conductivity in a wide temperature range and increasing the Li + transference number. Moreover, Balaish et al have reported that LAGP could provide adsorption sites for oxygen molecules followed by the reduction of oxygen and the formation of Li 2 O 2 , which confirmed that LAGP was an effective electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in LOBs. …”
Section: Introductionmentioning
confidence: 99%
“…It is proved that the introduction of some additives into the polymer is beneficial to reduce the crystallinity of the polymer. 6 For example, adding small-molecule plasticizers, such as small-molecule monomers, oligomers, and succinonitrile, into polymer electrolytes is an effective solution to improve ion conductivity; 7,8 however, it is usually accompanied by a reduction in the mechanical properties of the electrolyte. 9,10 The inorganic filler additives, such as Al 2 O 3 , SiO 2 , and oxide electrolyte powder, can improve the mechanical property to a certain extent, but their contribution to conductivity is limited compared to smallmolecule plasticizers.…”
Section: Introductionmentioning
confidence: 99%
“…It is proved that the introduction of some additives into the polymer is beneficial to reduce the crystallinity of the polymer . For example, adding small-molecule plasticizers, such as small-molecule monomers, oligomers, and succinonitrile, into polymer electrolytes is an effective solution to improve ion conductivity; , however, it is usually accompanied by a reduction in the mechanical properties of the electrolyte. , The inorganic filler additives, such as Al 2 O 3 , SiO 2 , and oxide electrolyte powder, can improve the mechanical property to a certain extent, but their contribution to conductivity is limited compared to small-molecule plasticizers. ,, Generally speaking, molecular design is an ideal way to prepare polymer electrolyte matrices with low density, high homogeneity, and high mechanical strength. When the designed molecule is combined with plasticizers, a polymer electrolyte with high mechanical strength and high ionic conductivity at room temperature can be obtained …”
Section: Introductionmentioning
confidence: 99%